Late endosomes promote microglia migration via cytosolic translocation of immature protease cathD - Liu, Yi-Jun (Sci Adv, 2020)
Organelle transport requires dynamic cytoskeleton remodeling, but whether cytoskeletal dynamics are, in turn, regulated by organelles remains elusive. Here, we demonstrate that late endosomes, a type of prelysosomal organelles, facilitate actin-cytoskeleton remodeling via cytosolic translocation of immature protease cathepsin D (cathD) during microglia migration. After cytosolic translocation, late endosome–derived cathD juxtaposes actin filaments at the leading edge of lamellipodia. Suppressing cathD expression or blocking its cytosolic translocation impairs the maintenance but not the initiation of lamellipodial extension. Moreover, immature cathD balances the activity of the actin-severing protein cofilin to maintain globular-actin (G-actin) monomer pool for local actin recycling. Our study identifies cathD as a key lysosomal molecule that unconventionally contributes to actin cytoskeleton remodeling via cytosolic translocation during adenosine triphosphate–evoked microglia migration.